The cost of no measures - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Early in 2003, fresh outbreaks of foot-and-mouth disease (FMD) were declared in Botswana and Mozambique.